Harmonized detail specification for fixed tantalum capacitors. Porous anode, solid electrolyte. Cylindrical insulated/non-insulated metallic case, polar/hermetic seal, axial terminations. Basic plus additional assessment level. (15th August 1981) - British Standards Institution,
No abstract available